Ketogenic Diet for Treatment 2-Year 9 Month Old Boy With Intractable Epilepsy - Wijaya, I Made Ananta; Putranti, Alifiani Hikmah; Mexitalia, Maria (RSUP Dr. Kariadi, 2019)
Background:The ketogenic diet (KD) is a high-fat, low-carbohydrate, and normal-protein diet that has been used for the treatment of medically refractory childhood epilepsy since the 1920s.The KD includes 80% fat, 15% protein, and 5% carbohydrate; the ratio of fat to carbohydrate plus protein ranges from 2:1 to 4:1.The purpose of the case report was to learn benefits and factors that influence the administration of the ketogenic diet in intractable epilepsy. Case:A 2-years 9 months old boy since 3 month of age the child begins seizure. Five month the child was diagnosed with epilepsy received one type of anti epileptic drug (AED). Seven months of age the child began control in outpatient clinic Neurology Department of Dr. Kariadi Hospital with a diagnosis of general epilepsy, were given 2 type of AEDs. Since10 month of age the child was given 3 type of AEDs. The child still often seizure, at 15 months was diagnosed intractable epilepsyand at 29monthof age, was programed to have long term EEG and KD during hospitalization. Conclusion:The administration of KD in 2-years9 months old boy with intractable epilepsyshowed benefits in reducing the frequency of seizures. Key word : Ketogenic Diet, Intractable Epilepsy, Child